2020
DOI: 10.1111/jen.12726
|View full text |Cite
|
Sign up to set email alerts
|

Survey of entomopathogenic nematodes and associate bacteria in Thailand and their potential to control Aedes aegypti

Abstract: Aedes aegypti is an insect vector that transmits several viruses affecting humans worldwide. Entomopathogenic nematodes (EPNs) and their symbiotic bacteria are organisms with the potential to control many insects. In this study, we did a survey aimed to identify EPNs and their symbiotic bacteria and evaluate the larvicidal activity of bacteria against Ae. aegypti. We collected 540 soil samples from 108 sites in Phitsanulok Province, lower northern Thailand. Baiting techniques and White traps were used to isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the identification of fabclavine derivatives described here might support recent studies that revealed Xenorhabdus and Photorhabdus strains having ascaricidal or larvicidal activity. Here, especially X. szentirmaii-, X. indica-, X. stockiae-, as well as X. stockiae-related isolates showed the best activity [18,19,47]. Although these strains were confirmed as fabclavine producers in our current study, future work is required to confirm fabclavines as the active compounds here as well (Table 3) [20].…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, the identification of fabclavine derivatives described here might support recent studies that revealed Xenorhabdus and Photorhabdus strains having ascaricidal or larvicidal activity. Here, especially X. szentirmaii-, X. indica-, X. stockiae-, as well as X. stockiae-related isolates showed the best activity [18,19,47]. Although these strains were confirmed as fabclavine producers in our current study, future work is required to confirm fabclavines as the active compounds here as well (Table 3) [20].…”
Section: Resultsmentioning
confidence: 56%
“…The general interest on Photorhabdus and Xenorhabdus increased in recent years, not only because of their large number of SMs, but also due to their easy-to-handle cultivation under laboratory conditions in combination with the accessibility for genetic manipulations such as genomic integrations or deletions [14][15][16][17]. Furthermore, recently published studies focused on the possible application of Photorhabdus and Xenorhabdus as biological pest control agents with and without the corresponding nematodes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by the identification of numerous species found in one study included S. websteri , S. khoisanae , H. indica , H. bacteri-ophora and H. baujardi [ 15 ], and subsequently, S. websteri reported from lower northern Thailand [ 16 , 17 ]. At present, 15 EPN species representing a variety of ecological soil types in different geographic regions of Thailand have been reported including, S. siamkayai , S. surkhetense , S. websteri (synonym S. carpocapsae ), S. scarabiae , S. kushidai , S. minutum , S. khoisanae , S. longicaudum , S. guangdongense , S. huense , S. sangi , H. indica (synonym H. gerrardi ), H. baujardi (synonym H. somsookae ), H. bacteiophora and H. zealandica [ 15 , 17 , 18 , 19 , 20 , 28 , 35 , 36 , 38 , 39 , 40 , 41 ]. In addition, three Steinernema isolates ( Steinernema sp.…”
Section: Discussionmentioning
confidence: 99%
“…namnaonensis and P. temperata subsp. temperata [ 18 , 19 , 20 , 28 , 38 , 40 , 43 ]. Recently, Photorhabdus australis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…To date, over 100 species of EPNs (Hunt, 2016) and approximately 30 species of their symbiotic bacteria (Tailliez et al ., 2010, Tailliez et al ., 2012; Ferreira et al ., 2013; Kuwata et al ., 2013) have been described. In Thailand, approximately ten species of EPNs have been reported in several different habitats (Stock et al ., 1998; Maneesakorn et al ., 2010; Thanwisai et al ., 2012; Vitta et al ., 2015, 2017; Muangpat et al ., 2017; Yooyangket et al ., 2018; Suwannaroj et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%